Morphological and Functional Changes in Hepatic System Precipitate Liver Disease in Elderly: Addressing Knowledge Gaps and Treatment Challenges - Dwicahya, Fatrian; Kholili, Ulfa (The Indonesian Society for Digestive Endoscopy, 2024)
Globally, the elderly population are more increasing each year. The enhancement of life expectancy is also followed by the enhancement of chronic illness, which one of them is liver disease. In elderly, there are also several physiological and biochemical changes in liver. Several studies show that the reduction of liver function will affect the severity of liver clinical manifestation in older people. This review article aims to discuss more about liver disease in older population. Hepatitis A in elderly has higher mortality and morbidity rates compared to young people. More over, the progressivity of acute hepatitis B to chronic hepatitis B is also greater in older people than young people. The treatments of hepatitis B and hepatitis C are safe and effective to be applied in elderly. Polypharmacy and fraility affects the elderly to be more susceptible to drug induced liver injury (DILI). This review aims to address knowledge gaps in understanding the morphological and functional changes in the aging hepatic system, their implications for disease progression, and the effectiveness of current therapeutic strategies. By critically analyzing recent evidence, we identify challenges in treating liver diseases in the elderly and highlight areas requiring further research.